How do I solve a simultaneous equation?

In a simultaneous equation, you have tow unknown constants. For example: 2x + y = 18; x − y = 6. To find out the values of each, you first need to find one. You do this by getting one constant on its own on one side of one equation: x - y = 6 can be changed to x = y + 6. This can be rewritten as x = (y + 6). This shows that x is the same as y + 6, so hopefully you can see how we can now plug in this expression into the OTHER equation: 2x + y = 18 can be rewritten as 2(y + 6) + y = 18. We can now solve this.2y + 12 + y = 183y = 6y = 2We can now plug the value of y into either equation to find x.x - y = 6x - (2) = 6x = 8

Answered by Nat L. Maths tutor

2742 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

How do you apply the multiplication law of indices?


A train travels for 240 minutes to travel a distance of 220 miles. Assuming the trains speed is constant, what is the train's speed in miles per hour?


How do I find the coordinates of the turning point of the graph: y=3x^2-6x+7 ?


f(x) = 3x - 2a || g(x) = 2ax + 1 || fg(x) = 2x + b/2


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences